Improving Laboratory Experiences in Engineering Education - Rathod, S. S.; Kalbande, D. R. (Journal of Engineering Education Transformations, 2016)
Laboratory classes are integral part of an engineering course. Laboratory sessions are primarily designed to develop proficiency in technical skills, provide an opportunity to place theory in context, develop critical thinking skills and promote enquiry based learning. Laboratory experiences will be paramount in developing our students as independent learners, researchers, critical thinkers and generators of knowledge. There are several reforms need to be implemented to improve student laboratory experiences. This paper suggests some of the methods that can be implemented in engineering institutes. This paper also presents the study of usage of online tools and rubric based laboratory assessment methodology adopted in electronics engineering course.